Orientação ambiental de jovens na cidade de Tubarão- SC - Ribeiro, Mirian Gorete (2013)
Abstract : The issues surrounding the preservation of the environment are related to the maintenance of life and survival of all beings on the planet and are related to the development and training of ethical citizens committed to environmental problems. The diagnosis of concepts, ideas and environmental attitudes of young people in a given context may suit as a tool for planning practices in environmental education which are effective in forming an ecological individual. This study aimed identifies the environmental orientation of young people between 10 and 19 years old of the city of Tubarão - SC. For that purpose, answered a questionnaire 442 students of the seventh year of elementary school to the third grade of secondary education, of public and private schools. A self-administered questionnaire was applied in collective situation, composed of 10 questions. The data analysis involved descriptive and relational statistics, accomplished using the Statistics Package SPSS 17.0 and theme/category-based content analysis, as proposed by Bardin (2009), with the help of Microsoft Excel statistical package. The results indicated a positive guidance for young people with the environment in two of the attitudinal dimensions investigated (affinity and cognition). Among the perceived environmental problems, the most frequently cited were related to pollution in general and problems with garbage. Also, care actions with the trash were among the most practiced. With regard to what they learned in school about the environment, the more elements that appeared were those related to environmental concern and management with garbage. Also there was a significant association, between the behavioral component and gender. It was argued that despites the results showed a positive position of the participants in relation to the cognition and affinity dimensions, the results of the perception of local environmental problems and the behavioral strategies adopted demonstrated the default of a contextual demand in individuals, in order that they can engaged actually in effective pro-environmental actions in their dwelling place. It is concluded that young people are potential environmental advocates, however, demonstrated known only a few strategies to preserve the environment. Besides, the lack of context demands present in the city represent a challenge to environmental education, in an effort to transform the environmental orientation of young people into effective and consistent actions. As indicators of the study to the actions in environmental education, it is emphasized that programs should consider the differences between the sexes and the context of habitation, as well as seeking creative ways to work in an interdisciplinary form with the environmental issues, making this an ongoing theme in the school context, for that environmental problems are not forgotten.